Qowaidul Fiqhiyah Dalam Penetapan Jadwal Adzan Dzuhur Dan Asar Di Kediri - Muhammad Baihaqi; Rafidah Farah; Urfi Dwi Anggarini (Muwafaqat: Journal of Islamic Law, 2025)
This study examines the practice of delaying the call to prayer (adzan) for Dhuhr and Asr in Pare, Kediri, as a social response to the agrarian and educational rhythms of the community. Employing a qualitative approach and qawaid fiqhiyyah analysis, the findings reveal that this temporal adjustment is not a deviation but a manifestation of fiqh responsive to local realities. Legal maxims such as al-‘ādah muḥakkamah, al-mashaqqah tajlibu at-taysīr, and maslahah mursalah form the normative basis for legitimizing this practice within the bounds of Sharia. The Syafi’i school offers a consistent yet contextually flexible methodological framework in addressing such socio-religious phenomena. This adjustment also aligns with the objectives of Islamic law (maqāṣid al-sharī‘ah), particularly in preserving religion (ḥifẓ al-dīn) and fostering congregational engagement. Thus, the delayed adzan in Pare reflects an adaptive, maslahah-oriented, and contextually grounded face of Islamic jurisprudence. This study advocates for a model of Islamic law that is not merely textual, but transformative and deeply rooted in the lived realities of the ummah.